(untitled) (Research, Society and Development, 2021)
Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. It is a preventable and curable disease, but despite this, it remains a serious threat to global public health, being the second cause of death among communicable diseases. The study aims to identify the prevalence and adherence to treatment related to the outcomes cure, abandonment and death from tuberculosis in the state of Goiás in the years 2016 to 2020. This is a cross-sectional epidemiological study of quantitative aspect through DATASUS/TABNET, using the variables, year of notification, year of diagnosis, year beginning of treatment, gender and closed situation involving healing, abandonment and death from tuberculosis and was. In this sense, the highest numbers of notifications occurred in the year 2018 and the lowest, in the year 2020. Regarding cure, treatment abandonment and death for tuberculosis in the indicated period, the highest percentages were: 79.35% in 2016, 22.74% in 2020 and 10.83% in 2020, respectively. Regarding gender, the highest percentage was male, being 74.27%, which were associated with a lower cure rate, higher treatment abandonment rate and a higher rate of deaths from tuberculosis, when compared to females, present in 25.72% of total cases. Therefore, the results show a significant percentage of cases with male gender predominance related to the lower cure rate, higher dropout rate and higher death rate.